A comprehensive kinetic simulation of different types of plant fibers: autocatalytic degradation mechanism - Ornaghi, Heitor L. [UNESP]; Ornaghi, Felipe G. [UNESP]; de Carvalho Benini, Kelly C. C.; Bianchi, Otávio (Springer Nature, 2019)
Kinetic analysis of the non-isothermal degradation of three different plant fibers has been performed using isoconversional model-free methods, model-fitting methods in order to establish if different kinetic approaches provide consistent kinetic parameters. It has been shown that these approaches provide consistent kinetic parameters and can be combined in such a way as to enhance the reliability and quality of each other and consequently the overall kinetic analysis. As a result, the most probable kinetic parameters for the non-isothermal degradation of three different types of plant fibers determined were autocatalytic-type mechanism, following recent literature. The reaction pathway followed the Waterloo’s mechanism. All models were compared with the most common solid-state reaction models using a powerful statistical tool. Activation energy of 180 kJ mol−1 was found for all degradation steps, suggesting that cellulose plays a major role on Arrhenius parameters. Hemicellulose and lignin seems to affect more significantly the reaction order. The potential of the kinetic parameters for reliable prediction has been noticed due correlation coefficient above 0.99.
Keywords: Kinetic predictions; Model-fitting kinetics; Model-free kinetics; Plant fiber